Modelling the economic effects of COVID-19 and possible green recovery plans: a post-Keynesian approach. (26th November 2021) - Pollitt, Hector; Lewney, Richard; Kiss-Dobronyi, Bence; Lin, Xinru
ABSTRACT: Only twelve years after the global financial crisis, in 2020 the world was again in economic crisis. This time around, the source of the crisis was the COVID-19 global pandemic, which has affected the economy differently than the global financial crisis. However, as they were in 2008–2009, conventional macroeconomic theory and models have once again been found wanting, and economists have again turned for insights to the work of Keynes and more recent post-Keynesian scholars. This paper explores a simulation of the macroeconomic impacts of COVID-19 using the E3ME macro-econometric model. It describes two potential recovery packages, one of which could be described as 'green'. The modelling shows that the green recovery package could support the global economy and national labour markets through the recovery period, outperforming an equivalent conventional stimulus package while simultaneously reducing global CO2 emissions by 12%. Key policy insights: A green recovery plan is assessed against a reference scenario with COVID-19. It outperforms a non-green recovery plan of comparable value, while also reducing CO2 emissions by up to 12% below the reference scenario (15% below no-COVID baseline). The policies in the green recovery plan provide different relative impacts. Car scrappage schemes that promote the uptake of electric vehicles have the largest impact on GDP and jobs. Renewables, energy efficiency and electric vehicle promotion all have large impacts on emissions. The green recovery plan boosts production levels in all sectors of the economy except for energy and utilities. It boosts the consumer services sector that has been most affected initially by the pandemic but also the investment sectors that could suffer longer-term damage.